VMAT2 knockout mice: Heterozygotes display reduced amphetamine-conditioned reward, enhanced amphetamine locomotion, and enhanced MPTP toxicity - Takahashi, Nobuyuki (The National Academy of Sciences of the USA, 1997)
The brain vesicular monoamine transporter (VMAT2) pumps monoamine neurotransmitters and Parkinsonism-inducing dopamine neurotoxins such as 1-methyl-4-phenyl-phenypyridinium (MPP(+)) from neuronal cytoplasm into synaptic vesicles, from which amphetamines cause their release. Amphetamines and MPP(+) each also act at nonvesicular sites, providing current uncertainties about the contributions of vesicular actions to their in vivo effects. To assess vesicular contributions to amphetamine-induced locomotion, amphetamine-induced reward, and sequestration and resistance to dopaminergic neurotoxins, we have constructed transgenic VMAT2 knockout mice. Heterozygous VMAT2 knockouts are viable into adult life and display VMAT2 levels one-half that of wild-type values, accompanied by smaller changes in monoaminergic markers, heart rate, and blood pressure. Weight gain, fertility, habituation, passive avoidance, and locomotor activities are similar to wild-type littermates. In these heterozygotes, amphetamine produces enhanced locomotion but diminished behavioral reward, as measured by conditioned place preference. Administration of the MPP(+) precursor N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine to heterozygotes produces more than twice the dopamine cell losses found in wild-type mice. These mice provide novel information about the contributions of synaptic vesicular actions of monoaminergic drugs and neurotoxins and suggest that intact synaptic vesicle function may contribute more to amphetamine-conditioned reward than to amphetamine-induced locomotion.